2017
DOI: 10.5507/bp.2017.034
|View full text |Cite
|
Sign up to set email alerts
|

Central venous catheter-related thrombosis in intensive care patients - incidence and risk factors: A prospective observational study

Abstract: Background. One of the complications associated with central venous catheter (CVC) placement is catheter related deep vein thrombosis (CR-DVT). However a literature search revealed little evidence of this recognised complication. The primary aim of this study was to establish the incidence rate and risk factors for the development of CR-DVT in our critically ill adult patients. Methods. All critically ill adult patients admitted to the medical-surgical ICU with CVC inserted were included in this observational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 26 publications
1
15
0
1
Order By: Relevance
“…The femoral vein seems to be a high‐risk location for catheter‐associated DVTs in the ICU . As in a recently published study, we observed that the internal jugular vein had most catheter‐related DVTs. This finding might be important since internal jugular vein thrombosis previously has been associated with high mortality and morbidity rates in ICU patients …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The femoral vein seems to be a high‐risk location for catheter‐associated DVTs in the ICU . As in a recently published study, we observed that the internal jugular vein had most catheter‐related DVTs. This finding might be important since internal jugular vein thrombosis previously has been associated with high mortality and morbidity rates in ICU patients …”
Section: Discussionsupporting
confidence: 87%
“…Limited data from ICU patients suggest that DVTs often occur in other locations than the lower extremities, and/or related to central venous catheters (CVCs) . Many VTEs in ICU patients are not clinically suspected, since clinical features may be absent or difficult to distinguish from other conditions.…”
Section: Introductionmentioning
confidence: 99%
“…We speculated that the results were affected by differences among the prophylactic anticoagulants used and their doses. The efficacy of antithrombotic prophylaxis for CRT is controversial 5 8 , 29 , and no clear benefit has been determined for critically ill patients who received anticoagulant prophylaxis for CRT. Hence, individualised risk and benefit evaluations are required.…”
Section: Discussionmentioning
confidence: 99%
“…The reported CRT rates vary widely depending on the study design, patient selection, catheter type and location, and other factors. Previous studies 2 4 reported CRT rates of 42–56% in the internal jugular veins of critically ill patients, but the efficacy of antithrombotic prophylaxis for CRT remains controversial 5 8 .…”
Section: Introductionmentioning
confidence: 99%
“…[2,5,6] There is a thrombosis rate of 25-30% of the IJV among all catheter placements; one study showed that IJV catheters have a 4 times greater risk of causing thrombosis than a subclavian catheter. [1,9,10] Another cause of a filling defect in IJV could be a primary leiomyosarcoma of the IJV. Leiomyosarcoma tumors are smooth muscle malignant tumor with higher occurrence in the inferior vena cava but can have intra-abdominal, subcutaneous, and vascular origin.…”
Section: Discussionmentioning
confidence: 99%